Penerangan Tambak Ikan dengan Panel Surya untuk Kemandirian Energi di Kabupaten Pangkajene dan Kepulauan - Hayat, Azwar; Salam, Nasruddin; Tarakka, Rustan; Aminy, Ahmad Yusran; Putra, Andi Erwin Eka; Sule, Luther; Arsyad, Hairul; Amaliyah, Novriany; ., Rudi (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
Turungan Bontojai Village is one of the areas in Pangkajene and Kepulauan Regency (Pangkep) where the majority of the people work as fish farmers or shrimp farmers. Administratively, this area is Sibatua Village, Pangkajene District. This village is an area close to the sea where infrastructure does not receive much attention, especially the electricity network. The electrical energy crisis experienced by the people of this village area needs a solution. In this community service activity, renewable energy from solar cells have been planned and applied to light the residents' ponds in Turungan Bontojaidengan Village. Lighting application with solar panels that will be placed in one of the residents' ponds as a pilot project for the application of the renewable energy. The community also received training on how to care for the equipment so that the community could independently maintain the sustainability of the program in the future. A 100 wp solar cell with a 432 Wh battery is installed to power 4 unit 7 watt light bulb with an additional DC to AC inverter which can be used to power other electronic equipment. The lights are operated at night for 12 hours with a total power consumption of 336 watts per day. Electronic devices are operated during the day by utilizing direct solar energy which is converted from DC current from solar cells to AC current using a 300 watt inverter. On a daily basis, benefits are obtained in the form of free electricity of 400 watts per day to meet the pond needs of the residents of Turungan Bontojai village. This activity has succeeded in increasing citizens' understanding as seen from the results of data processing with SPSS in the Pre-test and Post-test which shows an increase in understanding with a Mean value of 5.35 (pre-test) to 14.55 (post-test). The success of the activity was measured by a questionnaire on participant satisfaction with the community service activities carried out and the results showed that 90% were satisfied with the implementation of the activity.